Mindfulness-Based Cognitive Therapy (MBCT) Effectivity to Increase Positive Self Perception on Fatherless Adolescents - Amherstia Pasca Rina; Herlan Pratikno; Muchammad Rizal; Ricky Alejandro Martin (Universitas Negeri Surabaya, 2023)
Adolescence is said to be an unusual and challenging transitional period. Various kinds of problems involving youth groups are increasing day by day. Fatherlessness, or the loss of the father's role, is one of the problems. These various problems cause adolescents to tend to have negative self-perceptions. Therefore, positive self-perception among adolescents needs to be improved. This study aims to determine the effectiveness of MBCT to increase positive self-perception in fatherless adolescents. Participants in this study consisted of six adolescents who experienced fatherlessness and would receive the MBCT intervention. The research instrument consisted of the self-perception scale, adapted from Robbins. The data analysis technique in this study used the Mann-Whitney U Test with the help of SPSS. The results of the hypothesis test obtained a score of z = -2.491 with a significance of p = 0.013. This means that there is a significant difference in increasing self-perception among fatherless adolescents. The results of the effect size test are known based on Rank-biserial totaling 0.861. This means that there is a great influence of Mindfulness-Based Cognitive Therapy on increasing positive self-perceptions in fatherless adolescents. Then adolescents, so it is concluded that Mindfulness-Based Cognitive Therapy is effective in increasing fatherless adolescents' self-perceptions. Penelitian ini bertujuan untuk mengetahui kekuatan hubungan motivasi dan juga stres bekerja dengan work engagement secara masing-masing maupun simultan. Pendekatan kuantitatif dipakai dalam penelitian. Pengambilan sampel yang dipakai ialah metode sampel jenuh. Sebanyak 270 orang yang mengisi kuesioner dengan tingkat respon 17,21% dari total populasi. Metode analisis data memakai analisis deskriptif kuantitatif, korelasi sederhana dan korelasi berganda. Uji normalitas dan linearitas dipakai sebelum pengujian hipotesis. Temuan dalam penelitian ini ialah motivasi kerja berkorelasi positif dan kuat dengan work engagement. Stres kerja berkorelasi negatif dan lemah dengan work engagement. Motivasi dan stres kerja secara berbarengan berkorelasi positif dengan work engagement. Pihak perusahaan diharapkan memberikan pelatihan motivasi, meningkatkan tunjangan yang diberikan serta memberikan kebebasan dalam mengatur jadwal kerja dan cara bekerja agar karyawan lebih merasa terikat dengan pekerjaannya. Peneliti selanjutnya dapat menggunakan faktor yang memediasi hubungan antara stres kerja dengan work engagement guna menjelaskan lemahnya hubungan yang ditemukan dalam penelitian ini. Peneliti selanjutnya bisa juga membandingkan tingkat motivasi kerja, stres kerja dan work engagement pada karyawan yang memiliki posisi pekerjaan yang berbeda.